Coordination of soccer players during preseason training - Tessitore, A.; Perroni, F.; Cortis, C.; Meeusen, R.; Lupo, C.; Capranica, L. (The Journal of Strength and Conditioning Research, 2011)
This study aimed to verify whether coordination improves as a result of a preseason soccer training. During 5 experimental sessions (days 1, 6, 11, 15, and 19), 16 semiprofessional male soccer players (22.0 ± 3.6 years) were administered 3 specific soccer tests (speed dribbling, shooting a dead ball, and shooting from a pass) and an interlimb coordination test (total duration of a trial: 60 seconds), consisting of isodirectional and nonisodirectional synchronized (1:1 ratio) hand and foot flexions and extensions at an increasing velocity of execution (80, 120, and 180 b·min-1). Furthermore, subjective ratings were monitored to assess the recovery state (RestQ) of the players, their perceived exertion (rating of perceived exertion [RPE]) for the whole body, and the perceived muscle pain (rating of muscle pain [RMP]) for the lower limbs and the internal training load by means of the session-RPE method. The ratios between post and pretraining RPE and RMP increased only during the first 2 experimental sessions and decreased after the second week of the training camp (p = 0.001). The Rest-Q showed increases (p < 0.05) for general stress, conflict/pressure, social recovery, and being in shape dimensions. Conversely, decreases (p < 0.05) were observed for social stress, fatigue, physical complaints dimensions. Throughout the preseason, the players improved their speed dribbling (p = 0.03), Shooting from a Pass (p = 0.02), and interlimb coordination (p < 0.0001) performances. These coordination tests succeeded in discriminating coordination in soccer players and could integrate field test batteries during the whole soccer season, because they were easily and inexpensively administrable by coaches.